The Proceedings of the Coastal Sediments 2011 2011
DOI: 10.1142/9789814355537_0177
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Budget: Mississippi Sound Barrier Islands

Abstract: Historical shoreline and bathymetric survey data were compiled for the barrier islands and passes fronting Mississippi Sound to develop a regional sediment budget spanning a 90-year period. Net littoral sand transport along the islands and passes is primarily unidirectional (east-to-west). Beach erosion along the east side of each island and sand spit deposition to the west result in an average sand flux of about 430,000 cy/yr throughout the barrier island system. Dog Keys Pass, located updrift of East Ship Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…To be consistent with Byrnes et al (2012) who studied the Mississippi coastal system based on observed island changes for the period from 1917 to 2010, the hurricane hindcast encompasses the same period. By considering all categories 4 and 5 hurricanes that have occurred in the Gulf of Mexico and the hurricanes and tropical storms with wind speeds exceeding 39 mph which made landfall within 500 km of Ship Island 208 hurricanes remain.…”
Section: Approachmentioning
confidence: 58%
See 4 more Smart Citations
“…To be consistent with Byrnes et al (2012) who studied the Mississippi coastal system based on observed island changes for the period from 1917 to 2010, the hurricane hindcast encompasses the same period. By considering all categories 4 and 5 hurricanes that have occurred in the Gulf of Mexico and the hurricanes and tropical storms with wind speeds exceeding 39 mph which made landfall within 500 km of Ship Island 208 hurricanes remain.…”
Section: Approachmentioning
confidence: 58%
“…In the present study, the previous work (Byrnes et al, 2012;Rosati et al, 2009) in which this morphological cell is bounded in the East by the Fort Morgan Peninsula and in the West by Cat island is followed (here referred to as the Mississippi Coastal Cell or MCC).…”
Section: Study Objectivementioning
confidence: 64%
See 3 more Smart Citations